Treating agricultural non-point source pollutants using periphyton biofilms and biomass volarization. (1st January 2022) - Marella, Thomas Kiran; Saxena, Abhishek; Tiwari, Archana; Datta, Aviraj; Dixit, Sreenath
Abstract: Untreated domestic wastewater and agricultural runoff are emerging as a potent cause of non-point source (NPS) pollutants which are a major threat to aquatic ecosystems. Periphyton biofilm-based technologies due to their high growth rate, energy efficiency and low input costs offer promising solutions for controlling nutrient pollution in agricultural systems. In this study we employed periphyton floway to treat NPS pollution from the agricultural watershed. The process performance of outdoor single pass algae floway (AFW) was evaluated. Steady state average biomass concentration of 11.73 g m −2 d −1 and removal rate of nitrogen: 0.60 g m −2 d −1, phosphorus: 0.27 g m −2 d −1, arsenic: 9.26 mg m −2 d −1, chromium: 255.3 mg m −2 d −1 and lead: 238.6 mg m −2 d −1 was achieved. In addition, the microalgae and their associated bacterial diversity and dynamics were analyzed. The results revealed a high diversity and rapid variations in the microbiome structure with diatom and cyanobacteria dominance combined with high N fixing and P solubilizing bacteria during most of the operational period. Elemental analysis of periphyton biomass was done for its safe use as slow-release fertilizer. Biofuel feedstock potential and nanoparticle generation potential of the biomass were analyzed. This work highlights the potential use of periphyton biofilms in remediation and recycling of NPS pollutants with simultaneous resource recovery. Graphical abstract: Image 1 Highlights: Biofilm consortia significantly reduced runoff nutrients and heavy metals. Biofilm extracts can induce bio-based nano particle generation. Phycosphere bacterial diversity was analyzed in periphyton biofilms. Wastewater grown periphyton biomass potential as biofertilizer is assessed.